Predictors of Health-Oriented Lifestyle among Health Workers of Amol City - KHadijeh Akbarnejad Nashli; Azar Tol; Fereshteh Majlessi; Mahdi Yaseri; Hadi Alizadeh (Tehran University of Medical Sciences, 2017)
Background: health-oriented lifestyle in today's world is the best way for preventing illness and healthy life. This study conducted to determine the predictor ofhealth-orientedlifestyle in health workers of Amol city. Materials and Methods: This study was a cross-sectional research conducted on 222 persons of health workers of Amol city. Instrument was a questionnaire including two parts; demographic information was extracted through 15 questionsand the data collected fromthe reliable and valid questionnaire of lifestyle .Data collection. Health workers filled questionnaires in a self-declaration way. To data analyze,t-tests, Mann-Whitney, ANOVA or Kruskal-Wallis and logistic regression used. Data were analyzed statically using SPSS. Results: This study showed that there is a significant relationship between living place of Prairie village with dimensions of sport , malnutrition , self-care ; and malnutrition dimension in persons below 35, below diploma degree, suffering a chronic disease , suffering high blood pressure ;and tobacco and alcohol consumption dimension in individuals less than35 years;men with medical advice,sport,Malnutrition,tobacco and alcohol consumption ,Health of buying,daily mobility,proper nutrition and owning a personal car with the consumption of tobacco and alcohol dimension ,safety in driving,Health of buying . Conclusion: Considering that most of the health workers especially men do not behave based on the health-orientedlifestyle, some actions should be taken to change thebehaviorof these individuals, professional educationalworkshops or workshops that do not need to basic information shouldbe activated, because these individuals have health knowledge but do not behave according to this knowledge.